Grapevine and apple replant disease in Hungary - Molnár, P.; Véghelyi, K.; Balogh, I. (International Journal of Horticultural Science, 2004)
Field experiment was conducted to study the replant problems of grapevine and apple. Plantings were in three different fields: on virgin soil, on apple replant soil and on vine replant soil. Each field was planted with 60 pieces of grafted vine (variety Bianca on rootstock Berl. X Rip. T.K. 5BB) and 60 pieces of grafted apple (variety Gloster on rootstock MM. 106). Fungicide (BUVICID K with 50 % captan agent, 0.5 g/1 1 soil) and nematocide (VYDATE 10 G with 10 % oxamil agent, 0.03 g/1 I soil) treatments were used in the soil in order to identify the causal factor of the problem. Biological soil test was conducted to test 17 soil samples of II wine districts and vine growing fields in plastic pots, under shading net. No root pieces were left in the soil. Two bud-cuttings of the Bed. X Rip. T 5C rootstock varieties were used as test plants. In each case, samples were taken from the vineyard and from the virgin soil. One fourth of the soil from the vineyard was left untreated and the other three part was treated with nematocide, fungicide or heat. The results of the field experiment suggest that there was no problem growing grapevine after apple and apple after grapevine, but both species had been inhibited growing after itself. The fungicide and nematocide treatments did not succeed in determining the casual factor of the problem. Heat treatment of replant soil (in pot test) was useful in AS and VNS soils. Results of biological soil test suggest, that grapevine replant problem do not occur in every vineyard. In fifty percent of soils, no significant differences between the treatments for shoot length, weight of cane, length, diameter and wood:ratio of the fourth internode were observed. In one case, difference was not found in any of the measured characters. However, fruiting bodies of Roesleria pallida (Pers.)Sacc. and the mycelium of Rosellinia necatrix Prill. were observed in this sample. In other samples, there was no significant difference between the treatments, but nematode and fungus infection appeared to be involved in increased shoot growth in nematocide and fungicide treated plants (mycelium of Rosellinia necatrix was detected). In other samples, the fungus infection caused significant difference between the virgin, untreated and fungicide treated soils and infection of Rosellinia necatrix was observed.